Burnout among doctors in China through 2018: A protocol of systematic review and meta-analysis. Issue 37 (September 2019) - Zheng, Qin; Yang, Kun; Wang, Xue; Ou, Zhenghang; Su, Xiaopeng; Zhang, Jing; Qu, Miao
Abstract: Background: Burnout negatively impacts the mental and physical health doctors. More seriously, it leads to poor patient care. In China, the situation is severe and more efforts are needed to reveal the epidemiological characteristics of doctor burnout to develop improved strategies of alleviating it. Due to the large number of heterogeneous and sample size-restricted surveys currently published, meta-analysis and systematic reviews are critical to a thorough understanding of burnout among Chinese doctors. Methods: The Cochrane Collaboration criteria and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) will be followed to conduct and report the systematic review. We will conduct a comprehensive search on the data bases of China National Knowledge Infrastructure (CNKI), WanFang, PubMed, EMBASE, PsycINFO, and the Cochrane Library from their inception to December 2018. Prospective cohort and cross-sectional studies that described the prevalence of Chinese doctors' prevalence will be eligible for inclusion. The risk of bias and methodological quality of the included studies will be assessed using a risk of bias tool and the Cochrane guidelines for observational studies. A generalized linear mixed model framework with the Poisson likelihood and the log link function will be used to access the incidence rate ratio. Multivariate Poisson regression framework will be conducted to adjust modeling heterogeneity and confounders, like difference regions and time periods. The risk of bias, heterogeneity, and quality of evidence will be assessed in accordance with the aforementioned guidelines. Results: The primary outcome will be the prevalence and distribution of 3 dimension of burnout in Chinese doctors, and the second will be the difference of prevalence between difference regions and time periods. Discussion: This systematic review and meta-analysis will help us to reveal the prevalence, characteristics, timeline, and correlation between these factors in burnout; we expect our work may provide a scientific basis for further prevention and intervention of burnout in Chinese doctors, eventually to improve the quality of health care. PROSPERO registration number: CRD42018104249.